Financial leverage and profitability of the manufacturing industry of the canton of Cuenca, Ecuador - Borja Peñaranda, Lisseth Daniela (2022)
Objective: To establish the relationship between profitability and financial leverage of micro, small and medium-sized enterprises, within the industrial sector of the canton, Cuenca (Ecuador), in the period 2018-2020. Method: The research approach was quantitative with a non-experimental and cross-sectional design. With the information of 150 companies, the Pearson correlation was applied, in order to recognize the level of association of the variables. Results: There is a correlation between financial leverage and the profitability of companies. This relationship is differentiated by the size of the company and by the year of study, both in direction and magnitude. However, the results of the linear relationship between financial leverage and profitability for the set of micro, small and medium-sized companies are not robust. Conclusion: Although there is a linear relationship between financial leverage and profitability, it is not robust for micro, small and medium enterprises. Similarly, the common variability between financial leverage and profitability is low, perhaps because there are other elements, such as the company's line of business, type of assets and decisions, that have an impact on the results generated by companies.